Towards directive on damages for infringements of the competition law - Jelena Čuveljak (Zbornik Radova Pravnog Fakulteta u Splitu, 2014)
In the proceedings conducted by the competition authorities (ili ako ste mislili baš na našu agenciju, onda the Croatian Competition Agency umjesto „the competition authorities“), the injured third parties are not entitled to claim for compensation of damages incurred by infrigement of the competition law provisions so they have to turn to the courts in order to claim for compensation. However, there are only a few judicial proceedings conducted in this area of legal practice. Therefore, in the past ten years, the European Union has put efforts into detecting which specific rules of the tort law in the Member States are complicating and precluding the injured parties from being compensated for the incurred damages. These efforts produced the proposal for DIRECTIVE OF THE EUROPEAN PARLIAMENT AND OF THE COUNCIL on certain rules governing actions for damages under national law for infringements ofthe competition law provisions of the Member States and of the European Union. This proposal aims to abolish major obstacles that are preventing the reparation of damages and seeks to provide the minimum of legal protection for the citizens and entrepreneurs. The European Parliament had adopted the final draft of the proposal in an ordinary legislative procedure and submitted it to the European Council,but the European Council has not adopted this proposal in so far. The key legal issue in this subject matter is that this proposal deals with legal matters concerning the civil proceedings that are regularly governed by the jurisdiction of the Member States.